2014
DOI: 10.1245/s10434-014-3501-4
|View full text |Cite
|
Sign up to set email alerts
|

Are the Sendai and Fukuoka Consensus Guidelines for Cystic Mucinous Neoplasms of the Pancreas Useful in the Initial Triage of all Suspected Pancreatic Cystic Neoplasms? A Single-Institution Experience with 317 Surgically-Treated Patients

Abstract: The updated FCG was superior to the SCG for the initial triage of all suspected pancreatic cystic neoplasms. CLP in the LR(FCG) group can be safely managed conservatively, and those in the HR(FCG) group should undergo resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 26 publications
2
63
1
Order By: Relevance
“…The study by Goh et al 2 in this month's edition of Annals of Surgical Oncology corroborates many of the findings presented by the Boston group. In applying both the original SCG and also the revised Sendai guidelines of 2012 to 317 patients, all of whom underwent surgical extirpation of the CLPs, the authors found that the revised FCG have superior positive and negative predictive values for preliminary malignant/malignant lesions (88 and 92.5 %, respectively) compared with the SCG (67 and 88 %, respectively).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The study by Goh et al 2 in this month's edition of Annals of Surgical Oncology corroborates many of the findings presented by the Boston group. In applying both the original SCG and also the revised Sendai guidelines of 2012 to 317 patients, all of whom underwent surgical extirpation of the CLPs, the authors found that the revised FCG have superior positive and negative predictive values for preliminary malignant/malignant lesions (88 and 92.5 %, respectively) compared with the SCG (67 and 88 %, respectively).…”
supporting
confidence: 83%
“…The series of 317 patients with CLPs reported by Goh et al 2 in this issue of Annals of Surgical Oncology addresses the core of these diagnostic dilemmas-which criteria should be applied to CLPs as clinicians decide which lesions warrant pancreatic resection? The authors should be recognized for their large study size, systematic review, and thorough application of two widely utilized classification systems: the 2006 Sendai Consensus Guidelines (SCG) and the revised Sendai criteria, also referred to as the Fukuoka Consensus Guidelines (FCG).…”
mentioning
confidence: 99%
“…This is mainly due to the rapid advancement of knowledge in this field resulting in particular: 1) the improved understanding of the natural history and biological behavior of the different pathological entities which comprise pancreatic cystic neoplasms and 2) more accurate preoperative diagnosis of these neoplasms as a result of a better understanding of their individual morphological characteristics on imaging and the introduction of newer diagnostic modalities such as endoscopic ultrasonography with fine needle aspirate (EUS-FNA) [2][3][4]. In general, the management approach has trended from that of aggressive surgical resection [5] to a more selective approach whereby most cystic neoplasms are now managed via surveillance [1,[6][7][8]. Since the landmark paper by Compagno and Oertel [9]; the general consensus was that all mucinous neoplasms were potentially malignant or malignant and should be surgically resected whereas serous cystic neoplasms were benign and could be managed conservatively [2,10,11].…”
mentioning
confidence: 99%
“…The suspicious features were cyst size >3 cm, presence of symptoms, dilated main pancreatic duct (>6 mm), presence of solid component and/or a positive cyst fluid cytology [2,14]. The SCG has since been validated by several studies [2,6,7]. It is widely recognized that the main limitation of the SCG is its low positive predictive value (PPV) resulting in resection of many benign BD-IPMNs [2,15,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation